2018
DOI: 10.3390/genes9060292
|View full text |Cite
|
Sign up to set email alerts
|

LTBSG1, a New Allele of BRD2, Regulates Panicle and Grain Development in Rice by Brassinosteroid Biosynthetic Pathway

Abstract: Panicle architecture and grain size are two important agronomic traits which determine grain yield directly in rice. In the present study, a mutant named ltbsg1 (longer top branch and shorter grain 1) was isolated from the cultivar “Zhenong 34” (Oryza sativa L. ssp. indica) by ethyl methane sulfonate (EMS) mutagenesis. The target gene was studied through phenotype observation, genetic analysis, map-based cloning and functional analysis. The histocytological analysis indicated that the elongated top branch and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…Many grain-size/weight genes have been successfully cloned in plants including rice and Arabidopsis thaliana [ 4 6 ]. More recently, studies show that LTBSG1 regulates panicle and grain development in rice by brassinosteroid biosynthetic pathway [ 7 ]. OsGW2 , encoding a ring-type E3 ubiquitin ligase, affects grain width, weight and yield by regulating cell division [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many grain-size/weight genes have been successfully cloned in plants including rice and Arabidopsis thaliana [ 4 6 ]. More recently, studies show that LTBSG1 regulates panicle and grain development in rice by brassinosteroid biosynthetic pathway [ 7 ]. OsGW2 , encoding a ring-type E3 ubiquitin ligase, affects grain width, weight and yield by regulating cell division [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…OsDof12 overexpression downregulates two positive brassinosteroid signal regulators like OsBR11 and OsBZR1 for suppression of brassinosteroid action. In conformity, Qin et al (2018) found a brassinosteroid deficient mutant named ltbsg1 showing a longer top panicle branch and shorter grain size from indica rice cultivar Zhenong 34 developed by ethyl methane sulfonate mutagenesis. In the mutant rice amino acid variation (Glycine-Arginine) in the FAD (Flavin adenine dinucleotide)binding domain of delta (24)-sterol reductase precludes brassinosteroid biosynthesis by preventing the conversion of 24-methylenecholesterol (24-MC) to campesterol (CR) in the early stage.…”
Section: Brassinosteroid Interaction With Gibberellinsmentioning
confidence: 87%
“…A gif1 mutation shows slower grain filling and exhibits increased grain chalkiness on account of abnormally developed and loosely packed starch granules. The latest report on the molecular biology of grain size comes with the identification of a brassinosteroid-deficient mutant ltbsg 1 showing longer top branches in panicle and shorter grain (Qin et al 2018). In the wild LTBSG1 located on chromosome 10 is constitutively expressed and the proteins are found in the chloroplast, cell membrane and nucleus.…”
Section: Qtls For Grain Sizementioning
confidence: 99%